2009
DOI: 10.1007/s00280-009-1121-7
|View full text |Cite
|
Sign up to set email alerts
|

PSC833, cyclosporine analogue, downregulates MDR1 expression by activating JNK/c-Jun/AP-1 and suppressing NF-κB

Abstract: These results indicate that PSC833 not only sensitizes SK-MES-1/DX1000 cells to doxorubicin by enhancing drug accumulation, but also downregulates MDR1 expression by activating JNK/c-Jun/AP-1 and suppressing NF-kappaB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…It is well documented that many transcription factors, such as Ap-1, NF-kB, Akt and STAT3 are involved in activation of MDR1 gene in various cancers [24,25,26,27,28,29]. STAT3 binds to the potential promoter region, +64 and +72 of MDR1 in myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that many transcription factors, such as Ap-1, NF-kB, Akt and STAT3 are involved in activation of MDR1 gene in various cancers [24,25,26,27,28,29]. STAT3 binds to the potential promoter region, +64 and +72 of MDR1 in myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no effective treatment strategy to override these transporters for clinical therapy. In addition, several receptor-mediated survival signaling pathways, including mitogen-activated protein kinase (MAPK), Akt, mTOR, NF-kB, and Notch pathways, have been linked to the drug resistance of conventional chemotherapy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated that GUT-70 may be a useful agent for the treatment of leukemia 107 . Conclusively, it is important to note that, some substituents present on the basic coumarin structure, such as the substituents at position C 4 (28), C 5 (24), C 6 -C 7 (24, 25 and 28), ether at position C 7 (25, 26, 27 and 28) and a [a,b-di(hydroxyisopropyl)dihydrofuran] group at positions C 7 -C 8 (23), exhibit a significant inhibitory effect on P-gp 101 . For example, Jabeen et al 108 reported that heterocyclic substituents at position C 4 or C 3 -C 4 not only enhanced lipophilicity (or log P) but also showed higher inhibitory activity of P-gp.…”
Section: Coumarinsmentioning
confidence: 99%
“…However, inhibition of two or more ABC transporters leads to complicated drug-drug interactions by this class of compounds. These inhibitors include non-immunosuppresive analogs of cyclosporin A, valspodar 23 ; Disomer of verapamil, dexverapamil 24 . Others are MM36 25 , cinchonine 26 and quinine homodimer Q2 27 (Table 1).…”
Section: Introductionmentioning
confidence: 99%